2003
DOI: 10.1128/iai.71.11.6222-6228.2003
|View full text |Cite
|
Sign up to set email alerts
|

TheMIC3Gene ofToxoplasma gondiiIs a Novel Potent Vaccine Candidate against Toxoplasmosis

Abstract: Infection with the intracellular protozoan parasite Toxoplasma gondii causes serious public health problems and is of great economic importance worldwide. The micronemal protein MIC3, which is a potent adhesin of T. gondii, could be a significant candidate vaccine against toxoplasmosis. In this study, all CBA/J mice intramuscularly vaccinated with a plasmid encoding the immature form of the MIC3 protein (pMIC3i) produced specific anti-MIC3 immunoglobulin G (IgG) antibodies, and their sera displayed high antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 37 publications
(38 reference statements)
2
59
0
2
Order By: Relevance
“…4,22 The ROP8 vaccinated animals in our studies showed that antigenspecific spleen cells secreted high levels of IFN-γ. We also found that there is a significant correlation between the presence of high levels of IFN-γ secreting cells and degree of protection conferred.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…4,22 The ROP8 vaccinated animals in our studies showed that antigenspecific spleen cells secreted high levels of IFN-γ. We also found that there is a significant correlation between the presence of high levels of IFN-γ secreting cells and degree of protection conferred.…”
Section: Discussionmentioning
confidence: 92%
“…It may be possible to provide complete protection against T. gondii infection by combining ROP8 with other immunogenic proteins as previously described, such as ROP16, ROP18, MIC3, SAG1, and GRA4. 4,7,22,25,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antigen-specific IgG antibodies levels in serum samples were identified pre and post-treatment as previously described (Ismael et al, 2003). The TAg of T. gondii at 10 µg mL −1 was used to coat micro titer plates.…”
Section: Measurement Of Humeral Antibody Responses To Natural Infectimentioning
confidence: 99%
“…Recombinant GRA4 (rGRA4) combined with cholera toxin induced partial protection for immunized C57BL/6 mice against a nonlethal challenge with the 76K T. gondii strain (Leyva et al, 2001). Administration of a plasmid encoding the granulocyte macrophage colony-stimulating factor (pGM-CSF) enhanced the protection induced by immunization with plasmid encoding the protein MIC3 (Ismael et al, 2003). Co-inoculation of plasmids expressing GRA4 (pGRA4) and SAG1 (pSAG1mut) with pGM-CSF reduced mortality of susceptible C57BL/6 mice upon oral challenge with cysts of the 76K type II strain (Mévélec et al, 2005).…”
Section: Introductionmentioning
confidence: 99%